Using process redesign to improve DoD's environmental security program : remediation program management - Drezner, Jeffrey A. (RAND, 1999)
In fiscal year 1994, approximately $2.4 billion was spent on cleanup (or remediation) activities through the Defense Environmental Restoration Account and the Base Realignment and Closure act; in fiscal year 1996, approximately $2.1 billion will be spent, slightly less than half of the total Department of Defense (DoD) environmental security budget. Efforts to increase the efficiency of remediation activities, either by reducing costs or accelerating the process through simplification and streamlining, could have a substantial effect on DoD's ability to meet its cleanup obligations within an increasingly constrained budget. By examining the remediation management programs of two large chemical companies, Olin Corporation and DuPont, the authors identified activities DoD could implement to improve its remediation of thousands of sites at active and closing installations and formerly used defense sites. The following were the core identified tasks: Distribute responsibilities between the central management group and decentralized execution teams, adopt a business process perspective, include more-focused use of performance measurement, proactively identify and manage potential liabilities, and improve stakeholder (regulator and community) interactions.